Archiving a cultural heritage: the Nyonya Kebaya / Nalini Dharmarajan, Azhar Abdul Aziz and Anitawati Mohd Lokman - Dharmarajan, Nalini; Abdul Aziz, Azhar; Mohd Lokman, Anitawati (2006)
Malaysia is a multicultural society with a rich cultural heritage. It has a total population more than 21 million consisting of the Malays, Chineses, Indians, Kadazans, Dayaks, Bajaus, Melanaus, Muruts, Eurasians and aborigines (Shahar, 2000). Malaysia is multiracial, and these races live together to experiencing their own cultures and belief yet sharing it with others. Each of these cultures has vigorously maintained its traditions and community structures. They have also blended together to create contemporary Malaysia's uniquely diverse heritage. One example of the complexity with which Malaysia's immigrant populations have contributed to the nation's culture as a whole is the history of Chinese immigrants (Geographia; 2005). The first Chinese to settle in the straits, primarily in and around Malacca, gradually adopted elements of Malaysian culture and intermarried with the Malaysian community. Known as babas and nyonyas, they eventually produced a synthetic set of practices, beliefs, and arts, combining Malay and Chinese traditions in such a way as to create a new culture.